Harmonic Analysis of A DC Railway Traction with Uncontrolled 12 Pulse Rectifier - Andri Pradipta; Santi Triwijaya; Willy Artha Wirawan; Febri Pandu Wijaya; Pegah Hamedani (Journal of Railway Transportation and Technology, 2022)
In the topology of the DC traction substation there is a rectifier component which generally uses a 12 pulse rectifier type and the load is in the form of a trainset with a component in the form of a converter used for variable speed drives (VSD). The operation of the rectifier and the VSD converter load causes harmonics to appear on the AC input side, so anticipation needs to be done. Therefore, it is necessary to conduct an assessment related to DC traction substations to obtain good electrical power quality. The purpose of this study was to determine the electric power quality parameters of DC railway traction using a 12 pulse rectifier and a VSD converter load. This research was conducted by simulating a DC railway traction model with a 12 pulse rectifier and knowing the comparison of the system power quality between the VSD converter load and the resistive load as the basic reference for the traction substation work system of this model. System modeling is done using PSIM software. The results of the simulation are the parameters of the stability of the voltage, current, and system harmonics.